Higher social cue utilisation improves communication, reduces perceived workload, and improves performance amongst ad hoc dyads in simulated rail control. Issue 1 (2nd January 2020) - Yee, Daniel J.; Wiggins, Mark W.; Searle, Ben J.
Abstract: The objective was to examine whether ad hoc dyads with different collective social cue utilisation would record differences in performance and perceptions of workload during a simulated rail control task that incorporated distinct levels of demand. The frequency of two types of communicative statements was also examined as mediating factors: closing the loop and informative responding. A quasi-experimental design was employed using 40 dyadic teams. The results indicated that ad hoc teams whose members comprised higher social cue utilisation recorded relatively faster response times and perceived lower levels of workload, and engaged in a greater frequency of communicative statements that involved 'closing the loop' and 'informative responses'. Social cue utilisation also exerted an indirect effect on perceived workload through informative responding. The outcomes have theoretical implications for models of ad hoc team performance, and practical implications for the selection and training of teams that operate on an ad hoc basis. Practitioner summary: This study indicates that, in the context of simulation tasks requiring teamwork, higher social cue utilisation amongst ad hoc team members is associated with communication, workload perception, and overall performance.